27th Linzer Conference on Travel Medicine Annual Meeting of the Upper Austrian Society for Travel Medicine (Oberösterreichische Gesellschaft für Reisemedizin) Linz, Austria, 26 April 2025 - Haditsch, Martin; Küpper, Thomas (Health Promotion & Physical Activity, 2025)
As usual, the meeting took place at Linz, the beautiful town with its baroque buildings halfway between Vienna and Salzburg (Austria). The topics were sorted according to the following headlines: 1. Heights and depths. 2. Cause for concern. 3. Time is life. 4. Exceptional… The abstracts presented here are sorted alphabetically by names of the lecturers.